The Foreign Policy of Peru - St John, Ronald Bruce (Lynne Rienner Publishers, 2023)
St John systematically analyzes the strong link between the external and internal concerns that determine Peruvian foreign policy, demonstrating that domestic objectives and political considerations strongly influence, if not actually dictate, many aspects of the nation's international posture